Has Women's Participation in Local Government Been Strengthened? A Legal and Political Analysis in Riau Province? - Firdaus, Emilda; Artina, Dessy; Rauf, Muhammad A; Separen, Separen; Wijaya, Tommy Tanu (Journal of Indonesian Legal Studies, 2024)
This research delves into the critical role of women within the Village Consultative Body in Siak, Indonesia, with the aim of bolstering their involvement in local community empowerment endeavors. Employing a comprehensive sociological-legal research approach and drawing from a diverse array of data sources—ranging from primary field research to secondary and tertiary literature—the study offers profound insights into the multifaceted dynamics of women's roles within these bodies. Despite strides made in recent years towards gender equality, the study reveals persistent limitations hindering women's full participation in the Village Consultative Body. Cultural norms, deeply ingrained in societal structures, often perpetuate traditional gender roles, constraining women's agency in decision-making processes. Additionally, disparities in education levels and limited access to resources further marginalize women's involvement. However, amidst these challenges, the study illuminates the invaluable contributions of women to community development within the Village Consultative Body. Their participation not only brings diverse perspectives to the decision-making table but also fosters the development of better human resources within the community. In light of these findings, the study advocates for concerted efforts to bolster women's engagement in local governance structures. This includes initiatives aimed at challenging and reshaping entrenched cultural norms that inhibit women's agency, as well as addressing systemic barriers to education and resource access. Furthermore, recognizing the vital role of women in community development, the study underscores the need for targeted interventions to support and empower women within the Village Consultative Body. In conclusion, the research underscores the imperative of addressing the multifaceted challenges faced by women in their pursuit of equality and active participation in local developmental processes. By fostering an environment that values and amplifies women's voices and contributions, local governance structures can become more inclusive, responsive, and effective in addressing the diverse needs of their communities.